Туала удмурт проза: антология / [редактор-составитель С. В. Матвеев] - Матвеев С.В. (Удмуртия, 2020)
Экземпляры: СБ (20200731) / Инвентарный номер: 59604 / Цена: 355.00 / Сис.шифр: С(удм) / Авт.знак: Т 81 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Удм)